γδ T Cells and Tumor Microenvironment: From Immunosurveillance to Tumor Evasion - Lo Presti, Elena; Pizzolato, Gabriele; Corsale, Anna Maria; Caccamo, Nadia; Sireci, Guido; Dieli, Francesco; Meraviglia, Serena (Frontiers in Immunology, 2018)
γδ T cells possess cytotoxic antitumor activity mediated by production of proinflammatory cytokines, direct cytotoxic activity, and regulation of the biological functions of other cell types. Hence, these features have prompted the development of therapeutic strategies in which γδ T cells agonists or ex vivo-expanded γδ T cells are administered to tumor patients. Several studies have shown that γδ T cells are an important component of tumor-infiltrating lymphocytes in patients affected by different types of cancer and a recent analysis of ~18,000 transcriptomes from 39 human tumors identified tumor-infiltrating γδ T cells as the most significant favorable cancer-wide prognostic signature. However, the complex and intricate interactions between tumor cells, tumor microenvironment (TME), and tumor-infiltrating immune cells results in a balance between tumor-promoting and tumor-controlling effects, and γδ T cells functions are often diverted or impaired by immunosuppressive signals originating from the TME. This review focuses on the dangerous liason between γδ T cells and tumoral microenvironment and raises the possibility that strategies capable to reduce the immunosuppressive environment and increase the cytotoxic ability of γδ T cells may be the key factor to improve their utilization in tumor immunotherapy.